A Landscape of Medieval Common Peat Fens: The Lower Witham Valley and Wildmoor, Lincolnshire (UK). (3rd July 2021) - Gardiner, Mark
ABSTRACT: The peat fen was viewed by landscape improvers of the seventeenth and eighteenth centuries as under-utilised land in need of improvement. Two contrasting areas of common peat fen in Lincolnshire are examined to test this contention. It is shown that by the twelfth and early thirteenth century these fens were closely managed. To prevent flooding the adjoining rivers the watercourses were canalised. Drainage channels were cut through the fen to remove water and embankments were constructed to constrain the rivers. Some permanent settlements were established by monasteries in the twelfth century to use the rich pasture for cattle grazing. Other areas were enclosed for meadowland. Instead of considering these as poorly used wetlands which could not be drained, it is argued that their usage was adapted to the different conditions within the peat fens and that this allowed a range of resources to be exploited.